2022
DOI: 10.1128/aac.00243-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 16S rRNA Single Nucleotide Polymorphisms on Mycoplasma genitalium Organism Load with Doxycycline Treatment

Abstract: Doxycycline targets the 16S rRNA and is widely used for the treatment of sexually transmitted infections. While it is not highly effective at eradicating Mycoplasma genitalium infections, it can reduce organism load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…While there are no large clinical studies using minocycline for the treatment of M genitalium , randomized trials largely conducted over a decade ago consistently found that the tetracycline doxycycline was inferior to azithromycin in eradicating M genitalium with proportion cured in the order of 20%–40% [ 4 ]. However, no molecular mechanisms of resistance in the 16S ribosomal RNA gene have been found to consistently explain the low efficacy of doxycycline [ 22 ], and no correlation between MICs and microbial cure has been demonstrated [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there are no large clinical studies using minocycline for the treatment of M genitalium , randomized trials largely conducted over a decade ago consistently found that the tetracycline doxycycline was inferior to azithromycin in eradicating M genitalium with proportion cured in the order of 20%–40% [ 4 ]. However, no molecular mechanisms of resistance in the 16S ribosomal RNA gene have been found to consistently explain the low efficacy of doxycycline [ 22 ], and no correlation between MICs and microbial cure has been demonstrated [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited efficacy of doxycycline monotherapy for M. genitalium , with about one‐third of infections being cured, doxycycline is an important part of the current treatment regimen of resistance‐guided therapy and any reduction in efficacy of doxycycline for M. genitalium would have a substantial impact on the cure of an STI with already limited treatment options 30 . Although increases in doxycycline resistance have not been reported among small studies of M. genitalium , the molecular mechanisms of doxycycline resistance in this organism remain poorly understood, 31 precluding routine surveillance of doxycycline resistance in M. genitalium .…”
Section: Antimicrobial Stewardship Resistance and Microbiota Impactsmentioning
confidence: 99%
“…9,10 Similarly, M. genitalium has developed resistance to macrolide and fluoroquinolone antibiotics, with clinicians increasingly encountering infections that are difficult or impossible to treat. [11][12][13][14] To tackle the multifaceted problem of STI AMR, the Hub has four synergistic, cross-cutting research themes.…”
Section: The Exemplar Problem Of Sexually Transmitted Infections As P...mentioning
confidence: 99%